COVID-19 Critical Care Simulations: An International Cross-Sectional Survey - Temsah, Mohamad-Hani; Alrabiaah, Abdulkarim; Al-Eyadhy, Ayman; Al-Sohime, Fahad; Al Huzaimi, Abdullah; Alamro, Nurah; Alhasan, Khalid; Upadhye, Vaibhavi; Jamal, Amr; Aljamaan, Fadi; Alhaboob, Ali; Arabi, Yaseen M.; et al. (Frontiers in Public Health, 2021)
Objective: To describe COVID-19 simulations in international healthcare centers. Methods: This is cross-sectional, international survey among simulation team-leaders and healthcare workers (HCWs), based on each center’s debriefing reports from 30 countries in all WHO regions. The main outcome measures were the COVID-19 simulations characteristics, facilitators, obstacles and challenges encountered during the simulation sessions. Results: Invitation was sent to 343 simulation team leaders and HCWs who responded, 121 completed the survey. The frequency of simulation sessions was monthly (27.1%), weekly (24.8%), twice weekly (19.8%), or daily (21.5%). Among participants, 55.6% reported team’s full engagement in the simulation sessions. The average session length was 30–60 minutes. A total of 80% reported significant improvement in terms of clinical preparedness after simulation sessions, and 70% were satisfied with the COVID-19 sessions. Most perceived issues reported were related to infection control measures, followed by team dynamics, logistics, and patient transport issues. Conclusion: Simulation centers team leaders and HCWs reported positive feedback on COVID-19 simulation sessions with multidisciplinary personnel involvement. These drills are a valuable tool for rehearsing safe dynamics on the frontline of COVID-19.